(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2020)
This essay examines the role of agraphoi nomoi in Pericles’ funeral speech, particularly in the context of reflection on the Athenian politeia. Pericles’ choice to accentuate positively the role of agraphoi nomoi and underline the complementarity between written and unwritten nomoi deviates both from the rules of the logos epitaphios and from the contemporary debate on the nature of nomos, which affirmed the superiority of agraphos nomos as an expression of a universal and/or natural right. Conversely, Pericles affirms that the politeia of the Athenians assigns equal importance to written and unwritten laws and that the agraphoi nomoi are no less effective than the written ones in policing public behaviour, especially the disrespectful behaviour for what the Athenians considered worthy of respect (eusebeia). The agraphoi nomoi, as I argue here, were the ethe understood as customary norms and sacred regulations.